Are the suitors in the Odyssey guilty of rape? A linguistic analysis (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2019)
In book 22 of the Odyssey, just after the massacre of the suitors, Odysseus also has twelve maidservants executed, in part because they had engaged in sexual relations with his enemies. But in other passages we are told that the suitors would use force to get their way with female slaves (and Odysseus accuses them precisely of this crime in verse 22.37). This seeming contradiction has caused a great deal of confusion among commentators, translators and other modern readers. In this article I argue that there is no real reason for such confusion, which is based on an unwarranted reading of 22.37 as definite, that is, as though it implied that all slave women have behaved in the same way and that they have all been subjected to violence by the suitors. I also try to tease out, from the text of the Odyssey itself as well as some legal texts from classical poleis, which moral assumptions may have led the protagonist to behave as he does.